Employing Digital Resources to Improve Student Teachers Performance in Science - Eminah, Cosmos; Amoah, John Ekow; Appiah-Twumasi, Eric (European Journal of Applied Sciences, 2025)
The study is an action research that focused on the use of ICT-based resources to improve student teachers’ performance in selected concepts in science (Matter, Forces and Energy) within the four-year Basic Education Curriculum for Colleges of Education. The study was conducted in the Department of Basic Education, University of Education, Winneba. The sample consisted of 90 student teachers from one intact class. The main instruments for data gathering were tests (pre-test and post-test) on the three concepts of interest. Three research questions were formulated to guide the study. Findings of the study reveal that student teachers performance in each of the three concepts after the intervention. It was also revealed that there were statistically significant differences (P< 0.05) in the performance of student teachers before and after the intervention. The key recommendation made was the integral use of ICT in the daily teaching and learning of science by science lecturers and tutors in the University of Education, Winneba and Colleges of Education. It was also suggested that Universities and Colleges of Education should equip science student-teachers with knowledge and skills on how to access and operate ICT resources and services such as computers, projectors and internet connectivity to promote the effective usage of these resources in science teaching and learning at the basic level of education.